2000
DOI: 10.1095/biolreprod62.6.1763
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Interference Between Glucocorticoid Receptor and Estradiol Receptor Mediates the Inhibitory Effect of Cortisol on Fish Vitellogenesis1

Abstract: In oviparous species, the synthesis of vitellogenin (Vg) takes place in the liver according to a strictly estrogen-dependent mechanism that first involves an up-regulation of the estrogen receptor (ER) by its own ligand. However, reports from the literature indicate that in trout stress or cortisol may cause a reduction of cytosolic E2-binding sites in the liver and a decrease in plasma Vg levels. To investigate the mechanisms underlying these effects, in vivo and in vitro experiments were designed in rainbow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 47 publications
(64 reference statements)
1
53
2
Order By: Relevance
“…Although cortisol inhibited hepatic ER but not Vtg mRNA abundance in the present study, it is unclear whether this was GR specific, as RU486 also reduced ER transcript levels in trout. This agrees with results from another trout study demonstrating that RU486 did not inhibit the cortisol-mediated downregulation of ER (28). Indeed, vitelline envelope protein (a constituent of extracellular envelope around the growing oocyte) transcript levels, which are regulated by ER signaling (53), were also downregulated by cortisol and RU486.…”
Section: Modulation Of Estrogen-responsive Genessupporting
confidence: 90%
See 1 more Smart Citation
“…Although cortisol inhibited hepatic ER but not Vtg mRNA abundance in the present study, it is unclear whether this was GR specific, as RU486 also reduced ER transcript levels in trout. This agrees with results from another trout study demonstrating that RU486 did not inhibit the cortisol-mediated downregulation of ER (28). Indeed, vitelline envelope protein (a constituent of extracellular envelope around the growing oocyte) transcript levels, which are regulated by ER signaling (53), were also downregulated by cortisol and RU486.…”
Section: Modulation Of Estrogen-responsive Genessupporting
confidence: 90%
“…Vtg synthesis occurs in liver in response to ER activation by estradiol-17␤ in fish (16). Cortisol was shown to inhibit hepatic ER and Vtg expression, leading to impaired vitellogenesis in salmonids (28). Although cortisol inhibited hepatic ER but not Vtg mRNA abundance in the present study, it is unclear whether this was GR specific, as RU486 also reduced ER transcript levels in trout.…”
Section: Modulation Of Estrogen-responsive Genescontrasting
confidence: 52%
“…Therefore, IGF-1 and myostatin pathways might represent a first level of interaction between Dex and Estr, with the two hormones having opposite effects on such signaling pathways. GCs and estrogens have also been reported to act in opposition in the regulation of several physiological processes, both in vitro (e.g., 84,66) and in vivo (e.g., 33,58). Cross talk between GCs and estrogens appears to occur at several different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated in trout that activation of the glucocorticoid receptor by cortisol interferes with the ability of estradiol to stimulate transcription from the estrogen receptor, leading to decreased plasma vitellogenin levels [21]. Finally, studies have shown that glucocorticoid receptors and estrogen receptors are coexpressed in fish brain and pituitary [19,21]. Taken together, this information indicates a potential for interactions between the hypothalamus-pituitary-interrenal and the hypothalamus-pituitary-gonadal axes.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, information derived from studies examining the effects of cortisol and other stressors led to the hypothesis that synthetic glucocorticoids, such as dexamethasone, may have detrimental effects on teleost fish reproduction. Furthermore, it has been demonstrated in trout that activation of the glucocorticoid receptor by cortisol interferes with the ability of estradiol to stimulate transcription from the estrogen receptor, leading to decreased plasma vitellogenin levels [21]. Finally, studies have shown that glucocorticoid receptors and estrogen receptors are coexpressed in fish brain and pituitary [19,21].…”
Section: Introductionmentioning
confidence: 99%